Economic Sanctions and Agricultural Trade - Mario Larch; Jeff Luckstead; Yoto V. Yotov (Center for Economic Studies and ifo Institute (CESifo), 2021)
Combining two new datasets on sanctions and agricultural trade and implementing step-by-step the latest developments in the empirical structural gravity literature, we investigate the effects of sanctions on international trade of agricultural products. We find that trade sanctions have been effective in impeding agricultural trade, while other sanctions do not show any significant effects. The complete trade sanctions in our sample have led to about a 73% decrease in the agricultural trade between the sanctioned and sanctioning countries, or a corresponding tariff equivalent of 38.8%, but we also obtain significant estimates for partial sanctions. At the industry level, we find substantial heterogeneity depending on the sanctioning and sanctioned countries, the type of sanctions used, and the direction of trade flows. Focusing on the sanctions on Russia, we find that these sanctions substantially decreased bilateral trade of Russia, mainly due to reduced trade with the EU.
Keywords: F14; F51; Q17; 330; structural gravity; sanctions; agriculture; Russia; heterogeneity